Evaluating The Quality Of Islamic Civilization And Asian Civilizations Examination Questions - Rahimah, Embong; Ado, Abdu Bichi (2018)
Assessment of learning involves determining whether the content and objectives of education have been mastered by administering quality tests. Thus, the quality of the test items used in evaluating students’ achievement should be a major area of concern in teaching and research in the field of education. This paper assesses the quality of Tamadun Islam dan Tamadun Asia (TITAS) or Islamic Civilization and Asian Civilizations Examination Questions by conducting item analysis. The developed one hundred (100) multiple choices questions were administered to N=36 degree students. The data obtained had been analyzed by conducting item analysis in order to determine the item difficulties, item discrimination indices and the distractors analysis. The finding of results indicates that, based on difficulty indices 18(18%) items were “problematic” or “faulty”, 66(66%) of the items have poor discriminating power. Similarly, the result of the distractor analysis showed 59(59%) of the distractors been flawed, having failed to meet the set minimum standards. Based on the findings it could be assumed that the test used has not been validated during the item development processes. It is recommended that, TITAS test items used in measuring students’ achievement should be made to pass through all the processes of standardization and validation by conducting item analysis to ensure its reliability as well as to minimize measurement errors.